Impact of ESG Performance in Mitigating Non-Performing Loans in Kenya’s Commercial Banks - Gissay, Amadou; Mohamed Majid , Ruwaida (Universitas Negeri Semarang, 2025)
Purpose: The study examines the impact of ESG performance in mitigating non-performing loans of Kenyan commercial. Given the growing risks in Kenya associated with climate change and economic volatility in the financial sector, it is critical to understand how ESG performance can mitigate non-performing loans. Method: The study uses a dynamic panel system generalized method of moments model to analyse 33 commercial banks over the period 2013–2024. The non-performing loan (NPL) ratio is the dependent variable, while ESG performance is assessed across three key pillars: environmental, social and governance. Control variables include bank size, capital adequacy ratio and inflation rate. Findings: The study finds that there is a significant negative association between high ESG performance and non-performing loan ratios suggesting that enhanced ESG performance contributes to reducing non-performing loans. Novelty: The study adds to the knowledge of existing research on how ESG factor; environmental, social, and governance mitigates non-performing loans in Kenyan commercial banks thereby, enhancing scholarly discourse and offering insights for banking institutions and policymakers in their pursuit of sustainable financial practices.